Fully 3D printed electrochemical cell design with integrated electrodes array: A simple and versatile tool for sustainable electroanalysis - Roveda, Liriana Mara; Ottoni, Vitor Ferreira; Prado, Esmael Dias; Sequinel, Thiago; Suegama, Patricia Hatsue; de Carvalho, Cláudio Teodoro; Rodrigues, Raphael; Corazza, Marcela Zanetti; Trindade, Magno Aparecido Gonçalves [UNESP] (Elsevier, 2025)
3D printing technology has led to major advancements in the fabrication of intricate electrochemical systems, with reduced costs and less environmentally impactful approaches driving research in electroanalysis. In this work, we investigate the use of 3D printing technology to create fully 3D-printed electrochemical device — with integrated electrode arrangement — aiming to conform the principles of sustainability and green analytical chemistry. The device components — solution reservoir, cell top, and electrode holder — were created using commercial ABS filament and a 3D-FDM desktop printer. Electrodes, including the working (WE), auxiliary (AE), and pseudo-reference electrodes (PRE), were printed directly into the electrode holder cavities using a conductive CB-PLA filament with a 3D printing pen. The potassium ferrocyanide/ferricyanide redox couple was used to demonstrate some important principles of voltammetric techniques, evaluate the functionality of the electrochemical system, study the activity of the electrode array, and determine its electrochemically active surface area. As a proof of concept, this designed electrochemical cell was used to simultaneously determine paracetamol (AAP) and sodium diclofenac (DCF) in environmental water samples. Recovery percentages ranging from 71.0 to 108 % and 83 to 113 % with detection limits of 0.21 and 0.051 μmol L−1 were determined for AAP and DCF, respectively. These analytical results are comparable to those from previously reported modified electrodes used for AAP and DCF detection. However, the 3D-FPED offers inherent advantages of 3D printing technology, including rapid and straightforward prototyping and fabrication, design flexibility and material selection, scalability, low cost, accessibility, and sustainability. Finally, the analytical method developed with target device was assessed for environmental impact using the AGREE calculator, and the obtained scores demonstrated adherence to the principles of Green Analytical Chemistry.
Keywords: Diclofenac; Eco-friendly materials; Fully 3D-printed electrochemical device; Integrated electrodes; Paracetamol; Sustainability in additive manufacturing